Application of different lipid surfaces to monitor protein–membrane interactions by surface plasmon resonance spectroscopy. Issue 3 (2002) - Fischer Fischer, Torsten Torsten; Senin Senin, Ivan I. Ivan I.; Philippov Philippov, Pavel P. Pavel P.; Koch Koch, Karl-Wilhelm Karl-Wilhelm
Abstract : Planar lipid bilayers on sensor chip surfaces have become useful tools to study membrane bound processes by surface plasmon resonance spectroscopy. We immobilized phospholipids on sensor chips by different approaches. First, a self‒assembled monolayer of octadecylmercaptan was formed on a blank gold surface and subsequent addition of phospholipids led to formation of a heterobilayer. Second, a self‒assembled monolayer of mercaptoundecanoic acid was formed on a gold surface, the carboxy groups of mercaptoundecanoic acid were activated and covalently linked to phosphatidylethanolamine. Addition of phospholipids then led to a bilayer with phosphatidylethanolamine as the lower leaflet. Third, a hydrophobic sensor chip (L1, BIAcore) was used as a binding matrix for phospholipids. These lipid surfaces were tested, whether they are suitable to study proteinamembrane interactions. As biological test system we used the Ca 2+ ‒myristoyl‒switch of the neuronal Ca 2+ ‒binding protein recoverin. All three surfaces were sufficiently stable to monitor the Ca 2+ ‒dependent binding of recoverin to membranes.